MENINGKATKAN KEMAMPUAN MENGKLASIFIKASI MELALUI BERMAIN KONSTRUKTIF SIFAT PADAT - Vivi Ulandari; Sri Saparahayuningsih; Yulidesni Yulidesni (Universitas Bengkulu, 2018)
The problem of this research is how to improve the kids classifying ability trough playing the constructive solid nature can it improve the kids in group B PAUD Cempaka Putih Kabupaten Seluma in classifying ability. The aim of this research is to improve the kids classifying ability through playing the constructive solid nature. The kind of this research is classroom action research which was conducted in two cycles, each cycle was done by theree meeting with the subject was all the kids in group B Cempaka Putih with total number kids were 15 kids consist of 8 boys and 7 girls. The instrument of the research is observation by analizing the average data to know the level of successful the study. The result showed the kids classifying ability could be improved through playing the constructive solid nature. The data showed in first cycle 3,06 and in the second cycle showed the kids classifying ability improve to 3,9. The result of this research could be used for further research to improve the kids classifying ability through playing the constructive solid nature in different aspect. Keywords: classifying, playing, constructive solid nature.